Blepharitis in dogs: a clinical evaluation in 102 dogs. Issue 3 (4th March 2019) - Weingart, Christiane; Kohn, Barbara; Siekierski, Martina; Merle, Roswitha; Linek, Monika
Abstract : Background: Blepharitis is a common finding in many dogs with various skin diseases. Objectives: To establish a definition for canine blepharitis versus periocular dermatitis (POD), to evaluate the clinical findings and underlying skin diseases of blepharitis, and to document the effects of blepharitis on tear production in dogs. Animals: One hundred and two privately owned dogs with clinical signs of blepharitis and a definitive diagnosis of skin disease. Methods and materials: Prospective evaluation of clinical signs and underlying diseases in dogs with blepharitis alone compared to dogs with blepharitis and POD. Results: Brachycephalic dogs were significantly more likely to present with blepharitis than other breeds. Twenty five dogs had blepharitis alone [three dogs (2.9%) without and 22 dogs (21.5%) with cutaneous lesion beyond the periocular skin]. Seventy one of 102 (69%) presented with POD in addition to blepharitis. In six cases a differentiation between blepharitis and POD was not possible. Typical lesions included alopecia/hypotrichosis (97%), erythema (93%), eyelid oedema (50%) and crusts (39.2%). Allergic skin disease (52%) was the most common underlying cause of blepharitis, followed by infectious/parasitic diseases (21.5%), autoimmune disorders (17.7%) and neoplasia (4.9%). Four dogs could not be allocated to any of these disease groups. A diagnosis of parasitism was always accompanied by POD. Reduced tear production was detected in ten of the 53 dogs tested (18.8%). Conclusion: Blepharitis occurring in the absence of other skin lesions is rare. The most common underlying cause of blepharitis is allergic dermatitis. Measurement of tear production should be recommended in all cases of blepharitis. Abstract : Background – Blepharitis is a common finding in many dogs with various skin diseases.Objectives – To establish a definition for canine blepharitis versus periocular dermatitis, to evaluate the clinical findings and underlying skin diseases of blepharitis, and to document the effects of blepharitis on tear production in dogs.Conclusion – Blepharitis occurring in the absence of other skin lesions is rare. The most common underlying cause of blepharitis is allergic dermatitis. Measurement of tear production should be recommended in all cases of blepharitis.